PERBAIKAN PENGEMBANGAN TANAH MENGGUNAKAN ZAT ADDITIVE KAPUR DENGAN PEMODELAN ALAT KONSOLIDASI - Muhammad Jafri (UNIVERSITAS LAMPUNG, 2009)
There are lot of benefits can be obtained from lime, as mixture or filler, even it can be use as soilstabilization agent that is for clay stability. The experiment’s purpose is to know swelling andswelling pressure of clay when the addiction of lime applied. Test conducted in three phases, (1).physical test for clay and soil - lime mixture; (2). compaction test with modified proctor, and (3).swelling and swelling pressure test with load multiple of 17,67 kg. The soil sample is clay broughtfrom Gumbib Village at West Lampung and mixed with lime at 5%, 10%, and 15%. The resulttest that, the soil sample is classified in soft clay category (AASHTO and Unified). Another resultobtained that the usage of lime with certain procentage very effect to swelling and swellingpressure of clay. The addiction of lime applied, the swelling and swelling pressure of clay isdecreased. So it can be concluded that lime can be used as clay stabilizer.